(3CQHYhf MOjkKG efJbGI ef Sff CHj OGhOs - (3YHO Gddg Hf CMeO Hf jhSa GdRQfOis; (3SdjeGf Hf GdCTYK Hf GSMGb Hf HTjQ GdGROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s ((3eMeO Hf eMeO Hf CHj TQja GdTGaYi GdebOSi s)
(3ChdgG (B:s
(3gPg GMGOjK GfJbGgG YHO Gddg Hf CMeO Hf jhSa GdRQfOi ef Sff CHj OGhO GdSLSJGfi Yf YGFTI bGdJ bGd QShd Gddg Udi Gddg Ydjg hSde (B: " (3dGJbWYhG GddMe HGdScjf aEfg ef UfjY GdGYGLe hGfgShg aEfg CgfC s
(3BNQgG (B:s
(3hdG Jbhdgf ai eLdS NjQ heLdS PcQ EdG NJe dg Hgf Ydjg cGdNJe HGdNGJe Ydi GdUMjaI s
(3HgG fXGe GdJYbjHIs
(3YdjgG SeGY GdcGJH hLeGYI Ydi eMeO Hf YHO GdQMef GdeWQi GdGfUGQi HGdeSLO GdTQja hYdjgG NWI HUMI GdSeGYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
Keywords: (3GdMOjK h GdeUWdMs